Is there a Market for Microlending in Industrialized Countries? - Alexander S. Kritikos; Christoph Kneiding; Claas Christian Germelmann (European University Viadrina, Department of Business Administration and Economics, 2006)
While in less developed and in transition economies microlending has become an efficient instrument for providing small and micro businesses with the necessary financial means, in industrialized countries, with highly developed banking systems, the existence and size of an uncovered demand for microlending services has been controversially discussed. This study explores the inclination towards microlending products, with information drawn from 213 interviews conducted with German small and micro-business owners in 2005. Among the interviewed entrepreneurs, 15% report revolving funding needs and state that they are interested in microloans. Characteristic target group members are retail business owners, foreign small business owners, and persons having previously received private loans. Therefore, lenders entering the market should address this group using a focused market entry strategy. Key product features are a speedy access to short term loans combined with personal contact to the loan officer who should be able to thoroughly understand the client's business concept. Finally, it is also remarkable that 65% of the surveyed persons financed their first three years' operations without having asked for any loan product, at all. Among these, there might be a hidden demand which could be unleashed by designing novel microlending products.
Keywords: D12; G21; M31; 330; Microlending; Small Business Finance; Market Research; Mikrofinanzierung; Klein- und Mittelunternehmen; Finanzierung; Deutschland